If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + -2X) = 14 Remove parenthesis around (5 + -2X) 5 + -2X = 14 Solving 5 + -2X = 14 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2X = 14 + -5 Combine like terms: 5 + -5 = 0 0 + -2X = 14 + -5 -2X = 14 + -5 Combine like terms: 14 + -5 = 9 -2X = 9 Divide each side by '-2'. X = -4.5 Simplifying X = -4.5
| 144=-8(3x-6) | | 2(m-10)+2m-12+6+m/2=106 | | 4x+5=8x-9 | | (1/8)-x^2=0 | | m^2=1280 | | ex-n=kx-t | | 2(3x+1)-3(x-1)= | | 2x+20=120 | | 6x-5(7x+4)=165 | | 7+3(5)+42= | | 3(x+6)=66 | | 5+10x-8s= | | -90a^17b^11= | | 2x+36=18 | | 8x-35=47 | | -x-(14+4x)=-3(5-39x)+2 | | 3(2-x)=-18 | | 5-x=-7 | | 2x+3y=7y-13 | | Y-3y=8-6 | | (4y+7)-(6+3y)=6 | | -(5x+5)-(8x-7)=6-(4x+1) | | .50(16-x)=-12(x+7) | | -(b-7)-9(b-3)=8b-4b | | 3p-6p= | | 3(d+12)=-17p-5 | | -5y-y^2+4y^2-6y= | | Y+3y=8-2 | | (4+3i)(3i-4)= | | 0=(25x^2)/(x-2)+9-(2x)/(x-2) | | 7/5(-36/5r+1/4)+17/4=2077/150-5/6r | | 20+g=14 |